The Implementation of Tarekat Naqsyabandiyah Al Khalidiyah Wa Qodiriyah in Raden Rahmat Sunan Ampel Jember Islamic Boarding School - Zahro, Khanifatuz; Dahlan, Moh; Mislikhah, St (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Tarekat is a part of the implementation of tassawuf (mysticism) that has a tight connection with controlling carnality and concentrating on purifying the soul to get closer to Allah. It can even serve as a remedy for the dryness of the soul. This research employs qualitative approach with a type of field study research and have purpose to describe implementation of bai’at, zikir, suluk, and sunnah prayer in the Tarekat Naqsyabandiyah Al-Khalidiyah Wa Qodiriyah at Raden Rahmat Sunan Ampel Islamic Boarding School Jember. The research results indicate that the implementation of bai’at in this tarekat involves two steps: the bai’at of Tarekat Qodiriyah and the bai’at of Tarekat Naqsyabandiyah Al Khalidiyah. Before this, fasting, reading istighfar, taking a bath for repentance (taubat), taubat prayer, hajat prayer, and istikhoroh prayer are required. The implementation of zikr in this tarekat involves reading istighfar, sholawat, zikir nafyu isbat loudly, reading zikir ismu dzat and zikr nafyu isbat quietly, and also performing istighosah li tholabir ridho. The implementation of suluk in this tarekat requires fasting bi laa ruh for 10 days. The implementation of Sunnah prayer includes Taubat prayer, Lidaf’il Bala’ prayer, Istikhoroh prayer, Tahajjud prayer, Tabih prayer, Hajat prayer, Litsubutil Iman prayer, Birrul Walidain prayer, Witr prayer, and ends with prostration of gratitude.